A single cohesin complex performs mitotic and meiotic functions in the protist tetrahymena. - Rachel A Howard-Till (Public Library of Science (PLoS), 2013)
The cohesion of sister chromatids in the interval between chromosome replication and anaphase is important for preventing the precocious separation, and hence nondisjunction, of chromatids. Cohesion is accomplished by a ring-shaped protein complex, cohesin; and its release at anaphase occurs when separase cleaves the complex's α-kleisin subunit. Cohesin has additional roles in facilitating DNA damage repair from the sister chromatid and in regulating gene expression. We tested the universality of the present model of cohesion by studying cohesin in the evolutionarily distant protist Tetrahymena thermophila. Localization of tagged cohesin components Smc1p and Rec8p (the α-kleisin) showed that cohesin is abundant in mitotic and meiotic nuclei. RNAi knockdown experiments demonstrated that cohesin is crucial for normal chromosome segregation and meiotic DSB repair. Unexpectedly, cohesin does not detach from chromosome arms in anaphase, yet chromosome segregation depends on the activity of separase (Esp1p). When Esp1p is depleted by RNAi, chromosomes become polytenic as they undergo multiple rounds of replication, but fail to separate. The cohesion of such bundles of numerous chromatids suggests that chromatids may be connected by factors in addition to topological linkage by cohesin rings. Although cohesin is not detected in transcriptionally active somatic nuclei, its loss causes a slight defect in their amitotic division. Notably, Tetrahymena uses a single version of α-kleisin for both mitosis and meiosis. Therefore, we propose that the differentiation of mitotic and meiotic cohesins found in most other model systems is not due to the need of a specialized meiotic cohesin, but due to additional roles of mitotic cohesin.